Illicit substances use by Portuguese adolescents - Neto, Carla; Fraga, Sílvia; Ramos, Elisabete (Revista de Saúde Pública, 2012)
OBJECTIVE: To describe the prevalence of illicit drug consumption among adolescents and the motives that led these adolescents to try them. METHODS: Cross-sectional study with 2,499 adolescents aged 17 years, based on a cohort called EPITeen, which was started in 2003/2004 with adolescents born in 1990 who studied in public and private schools of the city of Porto, Portugal. A new assessment was carried out in 2007/2008: 1,716 adolescents (79.5%) were recovered and 783 new participants were evaluated. Information about social and demographic characteristics, family and personal history of diseases and behaviours were obtained through self-administered structured questionnaires. The chi-square test was used to test the associations. The statistical analysis was performed in the program SPSS® version 17. RESULTS: Of the adolescents, 14.6% had tried drugs at least once in their lives. The most tried illicit drug was cannabis (12.5%), followed by alcohol together with cannabis (5.5%) and tranquilizers (1.7%). The most cited reason for trying drugs was curiosity (77.5%). Friends were the most frequently cited form of obtaining drugs and the school was seen by 24.2% of the adolescents as a place where it was possible to buy cannabis. CONCLUSIONS: The results support the need to intervene at an early age and suggest that this intervention should be integrated with strategies targeted at other risk behaviors, particularly in schools.